Analisis Penerima Bantuan Sosial Terhadap Pengeluaran Konsumsi Non Pangan Rumah Tangga Miskin di Sumatera Barat - M. Arif Zhafran Zhafran; Novya Zulva Riani (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study is motivated by the predominance of food expenditure among poor households, highlighting the need to examine the factors influencing non-food consumption expenditure as an indicator of improved household welfare. The study aims to analyze the effect of social assistance and household socioeconomic characteristics on non-food consumption expenditure among poor households in West Sumatra Province. A quantitative approach was employed using data from the 2024 National Socioeconomic Survey (SUSENAS), which were analyzed using binary logistic regression. The independent variables include social assistance, educational attainment of the household head, employment status of the household head, gender of the household head, age of the household head, and area of residence. The results indicate that the educational attainment of the household head and the area of residence have a positive and statistically significant effect on the likelihood of poor households having higher non-food consumption expenditure. Meanwhile, social assistance, employment status, and the age of the household head do not have a statistically significant effect, whereas the gender of the household head has a negative effect and is only significant at the 10 percent significance level. These findings suggest that improvements in educational attainment and residential conditions play a more substantial role in increasing non-food consumption expenditure than the receipt of social assistance. Therefore, the government should enhance educational quality, expand access to economic facilities across regions, and improve the effectiveness of social assistance programs to better support the welfare of poor households